Siaran Berbudaya: Analisis Program Etnikom Sriwijaya Radio dalam Melestarikan Tradisi Lokal - Nayla Fatimah Azzarah; Badarudin Azarkasyi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
This study aims to analyze the role of Sriwijaya Radio Etnikom as a local media outlet in preserving regional language and culture in Palembang, South Sumatra. Amidst the currents of globalization and the dominance of national media, local radio holds significant potential to maintain cultural identity by broadcasting in regional languages and presenting content rooted in local wisdom. This research employs a descriptive qualitative approach, with data collected through in-depth interviews, observation, and document analysis. The findings indicate that Sriwijaya Radio Etnikom consistently airs programs in local languages such as Palembang and Malay, while also featuring cultural content including traditional music, regional specialties, and cultural discussions. The radio serves as an informal educational space that reintroduces cultural values to younger generations. Despite facing challenges such as declining interest among youth in regional languages and limited resources, Sriwijaya Radio strives to be at the forefront of local cultural preservation. Therefore, the role of local radio stations like Sriwijaya Radio Etnikom is crucial in sustaining cultural identity in the modern era.